PHYSICAL ACTIVITY OF WOMEN OVER 65 (Physical Culture and Sport: Scientific Perspective, 2023)
The evolution of civilization and progress in medicine have contributed to the extension of human life. Once unknown methods of treatment and modern pharmaceuticals significantly extend the individual's ability to maintain physical fitness in the field of cardiovascular, respiratory and musculoskeletal systems. These changes cause a noticeable change in the approach to life, as well as the willingness to actively participate in many group activities for which time was not previously found due to the burden of other professional duties. It can be observed that many people leave the implementation of their resolutions and passions until retirement age. In order for these plans to be implemented, one must be properly prepared for it, not only mentally but also physically. In the later stages of life, we use the acquired efficiency. Unfortunately, this state is not given to us for life. As in every living organism, aging processes begin after the age of 21, which in the initial stage are imperceptible. After the fifth decade of life, his hardships are felt [14]. Physical performance and mental state decrease. Difficulties with concentration and with the assimilation of new information are bothersome. Therefore, you should take care of your physical and mental condition, as it extends the period of fitness.The trend of physical activity has a positive effect on health, regeneration of physical and mental strength Systematic physical activity is a necessary condition for proper physical and mental development, good health, an important aspect of the prevention of civilization diseases, as well as an important element in the treatment of diseases and disorders. Numerous studies also prove that properly dosed physical activity is able to significantly reduce the negative impact of the aging process and maintain physical, mental and social health for as long as possible [7]. Taking up various forms of physical activity also gives the opportunity to meet new people, and thus greater certainty in social contacts [4].
Keywords: sport; health; seniors; education